Video Editing - Ricky Telg (EDIS, 2012)
Editing a video is a creative process where you put all the various parts together into one comprehensive program. Video editing software programs allow you to make changes easily. This 2-page fact sheet introduces the concept of video editing. Written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, June 2012.